HUBUNGAN FREKUENSI DAN LAMA PENGGUNAAN METAMFETAMIN DENGAN GEJALA PSIKOTIK PADA PASIEN DIRUMAH SAKIT KETERGANTUNGAN OBAT JAKARTA - Asyifa Widya Wardaningtyas (2020)
Methamphetamine is the most widely used type of drug in Indonesia. Methamphetamine is a psychotropic group I that can affect physical and mental effects on its users. One mental effect that is often associated with the use of methamphetamine is psychotic symptoms. Many factors of the use of methamphetamine can affect the emergence of psychotic symptoms, some of which are the frequency and duration of use of methamphetamine itself. Therefore, research related to the frequency and duration of use of methamphetamine with psychotic symptoms needs to be done. This study aims to determine the relationship of the frequency and duration of methamphetamine use with psychotic symptoms in patients at the Drug Dependence Hospital Jakarta in 2019. The sample of this study were patients who were undergoing outpatient and rehabilitation at the hospital during the study. This study uses an observational analytic design with a cross-sectional study approach using a methamphetamine use pattern questionnaire, while psychotic symptoms are determined by psychiatrist at the hospital. Sampling was done by total sampling method and get a sample of 30 patients. This study gave the result that there was no correlation between frequency (p = 0.796) and duration of use (p = 1.00) of methamphetamine with psychotic symptoms in patients at the Drug Dependence Hospital.